If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + 15 = 3 Reorder the terms: 15 + g = 3 Solving 15 + g = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + g = 3 + -15 Combine like terms: 15 + -15 = 0 0 + g = 3 + -15 g = 3 + -15 Combine like terms: 3 + -15 = -12 g = -12 Simplifying g = -12
| -8x^6-24x^5+224x^4= | | 4.2x+59.5=28.5-11.3x | | (5x^2+3x-2)+(2x^2+5x+19)-(7x^2-10)= | | (8+1x)*m=5m | | 100x=80 | | 20x-1/2x^2=50 | | -1/4*8 | | 17x=6800 | | 3-1/4x=x-7 | | 12b^2-21=0 | | 8(z-12)=3(2z+4) | | r^2+6rg-16g^2= | | 14-z=8 | | W-4= | | x + 14 x = 10 | | 40,000*90,000,000= | | 11/(12-8*3)+4 | | b^2+3b+88= | | v=3.14rh^2 | | 12x-19=2x+1 | | -9=-6y+3(y-8) | | 7.1+5-6.1=6 | | 3x-5i=xi | | 3(2x+1)=31/3 | | 63/-3 | | 440/60= | | 2+3ln(2x)=20 | | 7x+9=59+2x | | z+12z-48=0 | | 3n+14-2n=18 | | 2f+4s=5.9 | | 6x^2+1.5x-13.5=0 |